Changes in the lifestyle of Polish students as a result of the COVID-19 pandemic in the light of direct research - Waniowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The COVID-19 pandemic has caused significant changes in the lifestyles of all social groups. As a result of the subsequent restrictions resulting from the epidemic threat, all areas of both professional and private life had to be modified. Students were a social group whose lifestyle changes were particularly visible. For most of this period, universities conducted classes remotely, using Internet platforms. Therefore, it was necessary to make changes in the current way of life, often associated with a change of place of residence, modification of the way of spending free time and current habits. A significant part of these changes may be permanent and remain after the end of the pandemic state or threat. The aim of the paper is to analyze the changes in the lifestyle of Polish students in the light of our own surveys addressed to them. The students’ opinions on the changes in the way of acquiring and testing knowledge, in relations with the university and peers, and in the process of communicating with them will be presented and critically assessed. Changes in the process of nutrition, healthcare, including the length of sleep and physical activity, and the pursuit of one’s own interests will also be taken into account. The conclusions of the research will be confronted with the results of other studies and analyses devoted to various problems of lifestyle changes under the influence of COVID-19.
Keywords: pandemic; COVID-19; lifestyle